Actively Coping with Violation: Exploring Upward Dissent Patterns in Functional, Dysfunctional, and Deserted Psychological Contract End States - Schalk, René; De Ruiter, Melanie; Van Loon, Joost; Kuijpers, Evy; Van Regenmortel, Tine (Frontiers in Psychology, 2018)
Recently, scholars have emphasized the importance of examining how employees cope with psychological contract violation and how the coping process contributes to psychological contract violation resolution and post-violation psychological contracts. Recent work points to the important role of problem-focused coping. Yet, to date, problem-focused coping strategies have not been conceptualized on a continuum from constructive to destructive strategies. Consequently, potential differences in the use of specific types of problem-focused coping strategies and the role these different strategies play in the violation resolution process has not been explored. In this study, we stress the importance of focusing on different types of problem-focused coping strategies. We explore how employee upward dissent strategies, conceptualized as different forms of problem-focused coping, contribute to violation resolution and post-violation psychological contracts. Two sources of data were used. In-depth interviews with supervisors of a Dutch car lease company provided 23 case descriptions of employee-supervisor interactions after a psychological contract violation. Moreover, a database with descriptions of Dutch court sentences provided eight case descriptions of employee-organization interactions following a perceived violation. Based on these data sources, we explored the pattern of upward dissent strategies employees used over time following a perceived violation. We distinguished between functional (thriving and reactivation), dysfunctional (impairment and dissolution) and deserted psychological contract end states and explored whether different dissent patterns over time differentially contributed to the dissent outcome (i.e., psychological contract end state). The results of our study showed that the use of problem-focused coping is not as straightforward as suggested by the post-violation model. While the post-violation model suggests that problem-focused coping will most likely contribute positively to violation resolution, we found that this also depends on the type of problem-focused coping strategy used. That is, more threatening forms of problem-focused coping (i.e., threatening resignation as a way to trigger one’s manager/organization to resolve the violation) mainly contributed to dysfunctional and deserted PC end states. Yet, in some instances the use of these types of active coping strategies also contributed to functional violation resolution. These findings have important implications for the literature on upward dissent strategies and psychological contract violation repair.